Pembentukan Gairaigo dalam Terminologi Bola Voli: Studi pada Anime Haikyu!! - Nurhikmah, Nurhikmah; taqdir, Taqdir (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2026)
This study investigates the morphological formation of gairaigo in volleyball terminology as used in the anime Haikyu!! by Haruichi Furudate. The research aims to identify the types of word formation processes and the changes in word class that occur in loanwords adapted into Japanese. Employing a descriptive qualitative method, data were collected through observation and note-taking of dialogues in the first season of Haikyu!!. The data were analysed using a distributional approach to classify the forms and structural changes of gairaigo. The study identified 104 gairaigo items, most of which originated from English, with a smaller portion derived from Italian. The findings show that the dominant word formation processes include compounding, borrowing, affixation, and abbreviation. Furthermore, several gairaigo exhibited a shift in word class from nouns to verbs through the addition of suru and its conjugated forms. These results demonstrate the productivity of Japanese morphology in adapting foreign terminology, especially within the domain of modern sports. The study highlights how anime serves as a linguistic medium that reflects lexical innovation and the integration of global cultural elements into Japanese vocabulary.